Developing Expert System Application to Identify Specific Children Learning Disabilities in Inclusion Schools - Supriyadi Supriyadi; Dian Atnantomi Wiliyanto (Journal of ICSAR, 2021)
This study aims to develop an expert system application for the identification of specific children learning disabilities in Inclusion School. The research method used is development research design (R & D) to test the effectiveness of the use of identification of specific children learning disabilities with expert system application. Application testing was involving 40 teachers in inclusion schools to test expert system applications in identification. Validate results by teachers in inclusion schools were obtained that from aspects of system display, user, accuracy, and system responsibility have an average of 4.20 fall into the category of excellent.  Expert system application development has several features, among others; home menu, analysis, and intervention to follow up learning services, learning media, and classroom embedding for specific children learning disabilities.